2023
DOI: 10.1038/s41598-023-44433-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of different salt tolerant rhizobial inoculants in improving growth and productivity of Vigna radiata L. under salt stress

Qasim Ali,
Muhammad Shabaan,
Sana Ashraf
et al.

Abstract: Worldwide, salinity severely affects agricultural production of crops such as mung bean in arid and semi-arid regions. In saline conditions, various species of Rhizobium can be used to enhance nodulation and induce salinity tolerance in maize. The present study conducted a pot experiment to determine the efficiency of three rhizobial isolates under different salinity conditions, such as 1.41, 4 and 6 dS m−1, on mung bean growth parameters, antioxidant status and yield. Results revealed that salt stress imparte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…As a result, typically dormant stress-related genes are rapidly activated by environmental stress [ 15 ]. Plant interactions with environmental stress factors are known to contribute to the initiation of various defense mechanisms [ 16 , 17 ], resulting in qualitative and/or quantitative improvements in the development of plant metabolites, activation of hormone signaling pathways regulated by abscisic acid (ABA), salicylic acid, jasmonic acid, and ethylene, as well as reactive oxygen species (ROS) signaling pathways [ 18 ]. Furthermore, Abiotic stresses include cold, dryness, salt, and heavy metals mostly affect plant development and agricultural yield [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, typically dormant stress-related genes are rapidly activated by environmental stress [ 15 ]. Plant interactions with environmental stress factors are known to contribute to the initiation of various defense mechanisms [ 16 , 17 ], resulting in qualitative and/or quantitative improvements in the development of plant metabolites, activation of hormone signaling pathways regulated by abscisic acid (ABA), salicylic acid, jasmonic acid, and ethylene, as well as reactive oxygen species (ROS) signaling pathways [ 18 ]. Furthermore, Abiotic stresses include cold, dryness, salt, and heavy metals mostly affect plant development and agricultural yield [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mercury is ubiquitous, being found in all ecospheres as well as igneous rocks in trace quantities. Growing research has shown that Hg 2+ can be stored freely in advanced and aquatic plants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth-promoting rhizobacteria (PGPR) can support plant development through a variety of processes [5][6][7][8]. They can act directly by producing chemicals that stimulate growth and improve nutrient availability in the soil or indirectly by suppressing plant diseases in the rhizosphere [9][10][11]. Although research on PGPR in agriculture settings has progressed, much more research is needed on this group of bacteria in forest habitats [12].…”
Section: Introductionmentioning
confidence: 99%
“…Salt stress significantly decreases crop yields on infertile and partially fertile lands, leading to a reduction of over 50% in standard yields. This reduction in crop productivity is primarily attributed to the disruption of the plants' nutritional and water balance [ 7 10 ]. The ability of plants to withstand high salt levels is an intricate process, involving various factors such as morphological, physiological, and biochemical mechanisms [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%